Linking Exercise Intention to Exercise Action: The Moderating Role of Self-Efficacy - Hou, Bin; Li, Linqian; Zheng, Lei; Qi, Yating; Zhou, Song (Frontiers in Psychology, 2022)
As physical exercise benefits both physical and psychological health of college students, it is important to promote the habit of physical exercise among them. This study adopted the Health Action Process Approach (HAPA) model to understand the exercise intention–action link and determine the moderating role of self-efficacy. We recruited 242 students from a university in China and asked them to complete a six-wave survey. The survey results indicated that exercise intention was positively related to both coping planning and action planning, which pave the way to performing the action of exercise. However, such mediation effects varied under conditions of self-efficacy. Participants with high self-efficacy exhibited stronger relationships between intention and planning, and between planning and action. The study results suggest that planning has a time-lagged mediation effect in the relationship between intention and action. Additionally, the findings shed light on the moderating role of self-efficacy, which can be useful in developing health-promotion strategies for college students.